2000
DOI: 10.1002/(sici)1096-9071(200001)60:1<86::aid-jmv14>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Detection of neurotropic viruses circulating in Tuscany: The incisive role of Toscana virus

Abstract: Acute meningitis is perhaps the most frequent among central nervous system infections. We report a study considering 277 cases of meningitis hospitalized in the southern Tuscany area (Italy) during the period from 1995 to 1998 investigated by tissue culture and polymerase chain reaction (PCR) methods. The cytochemical analysis of the cerebrospinal fluid samples suggested the diagnosis of aseptic meningitis, recognized as viral meningitis in 104 cases by detection of viral DNA or RNA. The results collected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 35 publications
1
40
0
2
Order By: Relevance
“…2 Another phlebovirus, Toscana virus (TOSV), can cause meningitis, encephalitis, or meningoencephalitis in humans. [3][4][5][6][7] Human TOSV infection is reported in France, Portugal, Spain, and Italy. [8][9][10][11] TOSV belongs to the Naples serocomplex that also includes Sandfly Fever Naples virus (SFNV), the cause of a self-limited febrile condition known as phlebotomus, papatacci, or sandfly fever.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another phlebovirus, Toscana virus (TOSV), can cause meningitis, encephalitis, or meningoencephalitis in humans. [3][4][5][6][7] Human TOSV infection is reported in France, Portugal, Spain, and Italy. [8][9][10][11] TOSV belongs to the Naples serocomplex that also includes Sandfly Fever Naples virus (SFNV), the cause of a self-limited febrile condition known as phlebotomus, papatacci, or sandfly fever.…”
Section: Introductionmentioning
confidence: 99%
“…TOSV has been associated with acute meningitis and encephalitis occurring during the summer in individuals living in central Italy (1,7,12), Spain (3,6), and France (5), as well as in travelers returning from Mediterranean countries (2,4,10). TOSV infection in southern Italy has not been reported previously.…”
mentioning
confidence: 99%
“…TOSV was detected by a reverse transcription (RT)-nested PCR method. The primers were designed on the basis of a published sequence of the TOSV S segment-encoding N protein (GenBank accession number X53794), as previously described (9,12,13). The nested PCR products were labeled with digoxigenin and detected colorimetrically in microwell plates coated with a specific biotinylated capture probe by using a PCR-enzyme-linked immunosorbent assay digoxigenin labeling kit and a PCRenzyme-linked immunosorbent assay digoxigenin detection kit (Roche Diagnostics, Mannheim, Germany).…”
mentioning
confidence: 99%
“…Human cases of SFNV, mostly caused by Toscana virus, based on virus isolation and/or molecular evidence have been reported from North Mediterranean counties [6, 13-15, 24, 35-38]. The original Naples virus was identified for the last time in 1985 in Egypt from a human specimen [39].…”
Section: Discussionmentioning
confidence: 99%
“…The focus on Toscana virus occurred in the mid 1990's with several studies from central Italy where this virus was shown to be the most frequent cause of meningitis in central Italy during summertime [4-6]. The second event which highlighted Toscana virus was the systematic surveillance initiated in many South-European countries to track West Nile virus after it invaded the United States in 1999 and caused outbreaks in Europe and North Africa [7, 8].…”
Section: Introductionmentioning
confidence: 99%